TORAKOCHIRUGIAEarly and late results after sleeve lobectomies in patients with non-small cell lung cancer - Kasprzyk, Mariusz; Dyszkiewicz, Wojciech; Piwkowski, Cezary; Zieliński, Paweł; Pawlak, Krystian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Introduction: Pneumonectomy is frequently the only feasible type of resection in patients with centrally located non-small cell lung cancer (NSCLC). The resection of the entire lung increases the risk of serious postoperative complications and worsens the quality of life after surgery. In some cases, there is a possibility to avoid pneumonectomy and save a part of the lung through performing the sleeve resection of the bronchus. In comparison with pneumonectomy, the sleeve lobectomy could potentially increase the risk of local recurrence due to a shorter margin of bronchus without neoplastic infiltration. Aim: The aim of the study was to assess early and late results of the surgical treatment in patients with NSCLC following sleeve resections of the lobe. Material and Methods: We analysed a group of 85 patients surgically treated for NSCLC between 2001 and 2005. There were 70 males and 15 females, aged between 45 and 78 years (average 61). In each patient, the routine work-up and the assessment of the clinical stage of the disease preceded the surgery. The sleeve resections were performed under general anesthesia with a double-lumen endotracheal tube through an antero- or postero-lateral thoracotomy. Statistical analysis was performed using Statistica 7.1 software. The five year survival was calculated by the Kaplan-Meier method. Results: We performed right upper sleeve lobectomy in 53 cases, upper sleeve bilobectomy in 2 patients, left upper sleeve lobectomy in 23 cases and left lower sleeve lobectomy in 7 patients. In 13 cases of left upper sleeve lobectomy, an accompanying sleeve resection of the pulmonary artery was performed. The most frequent pathological type was the squamous cell lung cancer and the majority of patients were in IIB pathological stage of the disease. The postoperative mortality was 2.4%. The most common morbidities were supraventricular arrythmias (9.6%) and prolonged air leak (7.1%). The bronchopleural fistula developed in 2 cases. 56.5% of patients survived 5 years after the operation. Distant metastases were cause of death in 80% of cases. We confirmed local recurrence only in 2 patients. In multivariant statistical analysis, the N parameter of the TNM staging system was the only factor significantly affecting the five-year survival. Conclusions: The sleeve lobectomy seems to be a good alternative to pneumonectomy in selected cases of centrally localised tumors. Early and late results are encouraging and lung parenchyma’s saving resections certainly improve the quality of life after the resection.